PKM PENINGKATAN MUTU PANGAN LOKAL BERBASIS PANGAN FERMENTASI DI PULAU PAYUNG, KEPULAUAN SERIBU - Seprianto, Seprianto; wahyuni, Febriana Dwi (Jurnal Pengabdian Masyarakat AbdiMas, 2020)
AbstractThe Thousand Islands Region is administratively included in DKI Jakarta Province but has different characteristics from other DKI Jakarta areas. Payung Island is one of the islands in the Thousand Islands which is a marine tourism destination that is quite crowded with tourists. The diversity of processed products, especially fish-based products, is still little developed on this island, so there are not many choices for tourists. The purpose of this activity is to develop diversified food products by improving the quality of fermented-based local food. Through the cooperation of UMKMBarakuda Payung Island partners, the implementation of community service is going well. The method of implementation is by presentation and direct practice such as making peda fish, while other processed products such as bekasang and fish sauce were only a video documentary. A total of 13 members of the Barakuda group participated in this training. Processed products from fish have not been developed much by UMKM Barakuda, Payung Island. This activity also collaborates with the Product Design Team, so that it can provide an overview of the product from manufacturing to the packaging stage. It is expected that the implementation of this activity will increase the role of the community to be creative, innovative, independent, and entrepreneurial so that they can actively participate in regional and national development and become an attraction for tourists to visit the Thousand Islands. Keywords :Payung island, local food, fermentation food AbstrakWilayah Kepulauan Seribu secara administratif masuk ke dalam Propinsi DKI Jakarta, namun memiliki karakteristik yang berbeda dengan wilayah DKI Jakarta lainnya. Pulau Payung merupakan salah satu pulau di Kepulauan Seribu yang menjadi destinasi wisata bahari yang cukup ramai dikunjungi oleh wisatawan.Keberagaman produk olahan terutama berbahan dasar ikan masih sedikit dikembangkan di pulau ini, sehingga tidak banyak pilihan bagi wisatawan.Tujuan kegiatan ini adalah untuk pengembangan diversifikasi produk pangan dengan meningkatkan mutu pangan lokal berbasis fermentasi.Melalui kerjasama mitra UMKM Barakuda Pulau Payung, pelaksanaan pengabdian masyarakat ini berjalan dengan baik.Metode pelaksanaannya dengan presentasi dan praktek langsung seperti pembuatan ikan peda, sedangkan produk olahan lainnya seperti bekasang dan kecap ikan hanya berupa video dukumenter.Sebanyak 13 anggota kelompok UMKM Barakuda mengikuti pelatihan ini.Produk olahan dari ikan tersebut belum banyak dikembangankan oleh UMKM Barakuda Pulau Payung.Kegiatan ini juga berkalaborasi dengan Tim Desain Produk, sehingga dapat memberikan gambaran produk mulai dari pembuatan sampai pada tahap pengemasannya. Diharapkan dari pelaksanaan kegiatan ini akan meningkatan peranan masyarakat untuk kreatif, inovatif, mandiri, serta berwirausaha sehingga mampu berpartisipasi aktif dalam pembangunan daerah dan nasional dan menjadi daya tarik wisatawan untuk berkunjung ke Kepulauan Seribu. Kata kunci:Pulau payung, pangan lokal, pangan fermentasi